Pengaruh tekan kempa, temperatur, dan kadar lengas terhadap sifat fisikMekanik dan kualitas kayu sengon (paraserianthes falcataria=The Influence of Compression, Temperature and Moisture, - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
, Sengon (Paraserianthesfizicataria) is one among many chosen species planted in the industrial plantation forest. Sengon wood with an average specific gravity of 0.33, is classified as light wood, having low strength as well as low durability. Considering the wood quality is low while its supply is enough, then research on wood modification is needed to improve it for better utilization. The objective of the research is to investigate the increment of physical and mechanical properties to the increment in specific gravity by combination of compression, temperature, and moisture content. The research was conducted by involving three factors, namely compression (K), temperature (t), and moisture content (U). The first factor consisted of 5 levels: 0.00, 1.71, 2.56, 3.42, and 4.27 MPa, the second factor of 3 levels: 150, 175, and 200 Â°C, and the third factor 3 levels: 12, 18, and 24 %. Data were analyzed by factorial experiment in a completely randomized design (CRD), that comparisons were conducted by fully least significant difference (LSD). Result showed that the physical and mechanical properties were strongly influenced by increasing of compression, temperature, and moisture content. The three factors interaction effect was detected on the specific gravity, moisture content, static bending, shear, tension 1 to the grain, and compression II to the grain. The physical and mechanical properties tended to show positive correlation. Application of compression up to 4.27 MPa at a temperature of 200Â°C, resulted increased the specific gravity up to 89%